Nonlinear aging of cylindrical lithium-ion cells linked to heterogeneous compression. (February 2016) - Bach, Tobias C.; Schuster, Simon F.; Fleder, Elena; Müller, Jana; Brand, Martin J.; Lorrmann, Henning; Jossen, Andreas; Sextl, Gerhard
Highlights: Explanation for sudden increase in capacity fade refined. Graphite degradation and lithium loss are main degradation mechanisms. Compression differences accelerate degradation. Heterogeneity leads to local lithium plating. Plating induces strongly increased aging rates due to lithium consumption. Design and control measures against sudden degradation presented Abstract: Second-life applications of automotive lithium-ion batteries are currently investigated for grid stabilization. Reutilization depends on reliable projections of the remaining useful life. However, reports on sudden degradation of lithium-ion-cells near 80% state of health challenge these extrapolations. Sudden degradation was demonstrated for different positive active materials. This work elucidates the cause of sudden degradation in detail. As part of a larger study on nonlinear degradation, in-depth analyses of cells with different residual capacities are performed. Sudden degradation of capacity is found to be triggered by the appearance of lithium plating confined to small characteristic areas, generated by heterogeneous compression. The resulting lithium loss rapidly alters the balancing of the electrodes, thus generating a self-amplifying circle of active material and lithium loss. Changes in impedance and open-circuit voltage are explained by the expansion of degraded patches. Destructive analysis reveals that sudden degradation is caused by the graphite electrode while the positive electrode is found unchanged except for delithiation caused by side reactions on the negative electrode. Our findings illustrate the importance of homogeneous compression of the electrode assembly and carbon electrode formulation. Finally, a quick test to evaluate the vulnerability of cell designs toward sudden degradation is proposed.